Preliminary data on citrinin kinetics in humans and their use to estimate citrinin exposure based on biomarkers. (5th January 2018) - Degen, Gisela H.; Ali, Nurshad; Gundert-Remy, Ursula
Highlights: First data on kinetics of the nephrotoxin CIT and its metabolite DH-CIT in humans. Approximately 40% of the dose is found in urine as the sum of CIT and DH-CIT. Half-life: CIT 9.4 h (plasma), 6.7 h (urine); half-life: DH-CIT 8.9 h (urine). Exposure (biomonitoring data): below TDI in Europeans; exceedance in Bangladeshi. Abstract: Citrinin (CIT), a fungal metabolite causing nephrotoxicity, has a tolerable daily intake (TDI) value of 0.2 μg/kg bw. Contamination of food with CIT is not sufficiently known to allow dietary exposure assessment. Urinary biomonitoring data are available from cohorts of several countries. However, kinetic information is lacking for CIT, hampering the use of urinary biomonitoring data to estimate the daily intake. We have investigated the kinetics of CIT after oral intake in two human volunteers on two occasions. Urinary excretion showed that ingested CIT undergoes conversion to dihydro-citrinone (DH-CIT) which is then excreted in the urine along with parent compound. The cumulative urinary excretion within 24 h was between 32.9% and 70.8% (median 40.2%) of the sum of CIT and DH-CIT ('total CIT'). The median half-life in urine was 6.7 h for CIT and 8.9 h for DH-CIT. The median half-life in plasma accounted to 9.4 h. The daily urinary excretion for 'total CIT' served to estimate a provisional daily CIT intake using published urine biomarker data in several cohorts. European cohorts had an exposure well below the TDI whereas in Bangladesh the exposure in one cohort exceeded the TDI.